Analisis Yuridis terhadap Pertanggungjawaban Pidana Pelaku Pelecehan Seksual Berbasis Al (Deepfake Pornografi) di Media Sosial : Studi Kasus Mahasiswa Universitas Udayana Bali - Anggi Lia Liswati; Taun Taun (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The advancement of Artificial Intelligence (AI) technology has generated significant benefits while simultaneously creating new opportunities for cyber-based sexual offenses, particularly through deepfake technology, which enables the manipulation of a person's face into pornographic content without consent. This study examines criminal liability for perpetrators of AI-based sexual harassment and legal protection for victims in deepfake pornography cases, focusing on a case involving a student at Udayana University, Bali. This research employs a normative legal method by analyzing primary, secondary, and tertiary legal materials. The findings indicate that although Indonesian law does not yet explicitly regulate deepfake technology, perpetrators can still be prosecuted under the Electronic Information and Transactions Law, Pornography Law, Sexual Violence Law, and the new Criminal Code. Criminal intent is established through the deliberate manipulation, creation, and dissemination of non- consensual sexual content. Furthermore, victims are entitled to legal protection, including psychological recovery, privacy rights, restitution, and content removal. This study highlights the urgency of developing specific regulations addressing AI-related sexual crimes, enhancing forensic digital capabilities, and strengthening victim-centered protection mechanisms. The research contributes to the legal discourse on emerging digital crimes and emphasizes the need for adaptive legal frameworks in the AI era.